Isolation, Screening and Identification of Protease Producing Bacteria from Fish Sauce - Nguyen, Thanh Hang; Nguyen, Minh Thu; Nguyen, Ngan Ha; Le, Thanh Hai (Old Journal, 2019)
Proteolytic microorganisms in fish sauce are believed to play an important role in fish sauce fermentation. For better understanding their role in fish sauce fermentation and applying them back to the process, in this study the isolation and screening of protease-producing strain from fish sauce was investigated. The results showed that the proteolytic bacteria could be isolated on skim milk salt agar at salt concentration 5%, 7.5% and 10% but not at 20% or 25%. 33 isolates with halo was selected and was screened further by spot inoculation on skim milk salt agar at 5% and 10% NaCl and by enzyme diffusion method on skim milk agar at salt concentration 10%. All 9 isolates selected by high halo’s diameter D-d were gram positive spore forming rod and were identified as Virgibacillus halodenitrificants by 16s rDNA analysis with more than 99.2% homology. The strain Virgibacillus halodenitrificants CH201 possessed highest halo diameter 12.33 mm by enzyme diffusion method, following by CH322 9.33 mm. These two strains showed different profile of sugar utilization on API kit CH50.